Analýza ekonomických aktivit obcí - Poláková, Monika (Univerzita Pardubice, 2006)
Bakalářská práce se zabývá možnostmi podnikatelského chování obcí a konkrétními výsledky municipalit v této oblasti na příkladu šesti obcí.

The bachelor work Economics activities of selected municipalities is engaged in posibility business conduct of municipalities and in factual results in this area. It is described on the sample of towns.
Economic activities of municipalities
Keywords: economic activities; services; municipalities; ekonomické aktivity; služby; Pardubice; Jihlava; Chrudim; Litomyšl; Holice; Lázně Bohdaneč; obce